Structuring improved work environments for newly-qualified radiographers. Issue 1 (February 2020) - Chipere, T.G.A.; Motaung, T.; Nkosi, B.
Abstract: Introduction: Newly-qualified radiographers often struggle with workplace integration. Frequently, their workplace environments stifle professional growth, leaving them frustrated and anxious. This results in poor workplace performance and possibly even attrition, hence the need to strategically structure their workplace environments for easier transition. In South Africa, no published studies exist detailing the workplace transition process for new radiographers, and the environmental requirements. This paper investigates the needs of this group, to provide information on how to create improved working environments which will encourage retention of newly-qualified radiographers. Methods: Criterion sampling was used to select five hospitals, and total sampling to select all newly-qualified radiographers at the selected hospitals. After obtaining ethical approval and participant consent, seven newly-graduated radiographers were interviewed utilising a phenomenological approach. One-on-one, face-to-face interviews were conducted, audio recorded, and transcribed verbatim. Interpretive phenomenological analysis was performed on the resultant dataset to identify themes. Results: Four main themes emerged: interpersonal relations, support from fellow newly-qualified peers, departmental policies, and learning. Positive interpersonal relations were an essential component of the work environment; fellow newly-qualified radiographers at the same institution resulted in increased support; departmental policies needed to cater to the needs of new employees, and the environment must facilitate learning. Conclusion: While a positive workplace environment is desirable for all radiographers, newly-qualified graduates have specific needs which require attention. Management has a crucial role to play in ensuring that such an environment is created to encourage new radiographer retention. Highlights: Interpersonal relations form the crux of workplace environments. Support levels determine how well integration occurs. Policy needs to be structured around integration of new employees. Environments need to facilitate learning.